KOMPLEMEN IDEAL FUZZY DARI NEAR-RING - Saman Abdurrahman (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2013)
This paper introduces the concept of conformation of the ideal fuzzy near-ring and ideal anti-fuzzy near-ring, and the relationship between the ideal fuzzy near-ring and its con- struction. The result of this study is that if α is the fuzzy ideal of the near-ring, then αc is the ideal fuzzy anti-near-ring, and also the opposite